2013
DOI: 10.1097/ftd.0b013e31829a78c3
|View full text |Cite
|
Sign up to set email alerts
|

Methadone and Illegal Drugs in Hair From Children With Parents in Maintenance Treatment or Suspected for Drug Abuse in a German Community

Abstract: Altogether, investigation of children's hair proved to be a useful way to detect endangering drug use in their environment and lead to a more thorough inspection and measures to improve their situation in many of the cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 66 publications
0
34
0
Order By: Relevance
“…Table 1 presents studies using LC-TOF MS or LC-QqTOF MS for studying human exposures to a broad spectrum of environmental chemicals (Baduel et al, 2015, Cortejade et al, 2016, Diaz et al, 2012, Andra et al, 2015), and specifically for polycyclic aromatic hydrocarbons (Bouchard et al, 2009, Marchese et al, 2004), pesticides/insecticides (Cequier et al, 2014, McMahen et al, 2015, Taira et al, 2013, Yamaguchi et al, 2012), drugs (Chittamma et al, 2013, Pragst et al, 2013, Ristimaa et al, 2010, Marin et al, 2014), polyfluorinated chemicals (Eom et al, 2014, Rotander et al, 2015), environmental tobacco smoke (Swinton DJ., 2011), antibiotics (Wang et al, 2015, Wang et al, 2014a), and personal care products (Wu et al, 2012). GC-TOF MS or GC-QqTOF MS was primarily applied for studying human exposures to persistent organic chemicals (Hernández et al, 2009b, Kazda et al, 2004, Focant et al, 2004, Megson et al, 2015, Fan et al, 2014).…”
Section: Applications Of Time-of-flight Mass Spectrometry For Studmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 presents studies using LC-TOF MS or LC-QqTOF MS for studying human exposures to a broad spectrum of environmental chemicals (Baduel et al, 2015, Cortejade et al, 2016, Diaz et al, 2012, Andra et al, 2015), and specifically for polycyclic aromatic hydrocarbons (Bouchard et al, 2009, Marchese et al, 2004), pesticides/insecticides (Cequier et al, 2014, McMahen et al, 2015, Taira et al, 2013, Yamaguchi et al, 2012), drugs (Chittamma et al, 2013, Pragst et al, 2013, Ristimaa et al, 2010, Marin et al, 2014), polyfluorinated chemicals (Eom et al, 2014, Rotander et al, 2015), environmental tobacco smoke (Swinton DJ., 2011), antibiotics (Wang et al, 2015, Wang et al, 2014a), and personal care products (Wu et al, 2012). GC-TOF MS or GC-QqTOF MS was primarily applied for studying human exposures to persistent organic chemicals (Hernández et al, 2009b, Kazda et al, 2004, Focant et al, 2004, Megson et al, 2015, Fan et al, 2014).…”
Section: Applications Of Time-of-flight Mass Spectrometry For Studmentioning
confidence: 99%
“…The first step in HRMS software uses an Extracted Ion Chromatogram (EIC or XIC) or Extracted Mass Chromatogram (EMC) for spectral information display. Peaks from background noise and co-eluting peaks along with the extracted ions of interest are included within the same retention time window (Andra et al, 2015) (Pragst et al, 2013) (Pelander et al, 2008). The MS/MS filters that were described in the above section are also applicable for full-scan MS data reduction.…”
Section: High Resolution Data Extraction Features For Scaling Thementioning
confidence: 99%
“…Pragst et al [25] demonstrated that investigation of children's hair proved to be a useful way to detect endangering drug use in their environment and lead to a more thorough inspection and measures to improve their situation in many of the cases. Hair analysis could be a suitable way to examine this endangering exposure to drugs.…”
Section: Case Reportsmentioning
confidence: 99%
“…However, there are many publications in the last few years where the extraction method for chromatographic methods used is a simple methanolic extraction with direct injection, with no sample cleanup with the traditional SPE [67,73,76,78,81,82,84]. Domínguez-Romero and coworkers in 2011 evaluated three different methods of extraction and found that direct methanolic extraction was the most efficient method for extraction when compared with acidic or alkaline extraction followed by SPE cleanup procedure [74].…”
Section: Extractionmentioning
confidence: 99%